Pengaruh Jenis Kapur terhadap pH, Al Dapat Dipertukarkan, Kelarutan Fe, Ketersediaan Fosfor dan Kapasitas Tukar Kation di Lahan Pasang Surut - Rada Febriani; Fadly Hairannoor Yusran; Ratna Ratna (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2024)
Tidal land has low P availability due to soil acidity (pH) and the high fixation of Al and Fe into complex compounds. This study aims to determine the effect of dolomitic lime, calcite, and tohor (quicklime) on the soil pH, exchangeable Al, soluble Fe, available P and cation exchange capacity (CEC) in tidal land. The research method used was a one-factor Completely Randomized Design (CRD). The factors tested were the type of lime with three different doses (10 treatments) including control, 1.6, 2.7, and 3.9 t dolomite ha-1, 3.0, 5.0, and 7.0 t calcite ha-1, and 1.9, 3.2, and 4.5 t quicklime ha-1. The results showed that the application of various types of lime had a significant effect on pH, exchangeable Al, soluble Fe, available P, and CEC. The quicklime application at 4.5 t ha-1 increased the soil pH, solubility of P, CEC significantly and decreased exchangeable Al and available Fe compared to dolomite and calcite.